Nutritional Content Of Moringa Leaf (Moringa Oleifera) Fragrant Tea - Aini, Latifa; Daulay, Diana Pebriani; Anggraini, Anna (JURAGAN - Jurnal Agroteknologi, 2024)
Moringa leaf fragrant tea is tea that is prepared from the leaves of Moringa oleifera plant using the same manufacturing method as the process for making green tea and then added with jasmine flowers for 18 hours to give the tea a jasmine aroma. Moringa fragrant leaf tea has high antioxidant content, namely 71.58%. This research was conducted to look at the nutritional content of fragrant Moringa leaves. From the observations it was found that the fragrant Moringa leaves tea contained 26.48% protein, 1815 mg/100g calcium, 39.45% iron, 101.11 mg/100g carotene, 101.17mg/100g ascorbic acid and were positive contains alkaloids